Productivity differences - Acemoglu, Daron 1967-; Zilibotti, Fabrizio 1964- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1999)
Many technologies used by the LDCs are developed in the OECD economies, and as such are designed to make optimal use of the skills of these richer countries' workforces. Due to differences in the supply of skills, some of the tasks performed by skilled workers in the OECD economies will be carried out by unskilled workers in the LDCs. Since the technologies in these tasks are designed to be used by skilled workers, productivity in the LDCs will be low. Even when all countries have equal access to new technologies, this mismatch between skills and technology can lead to sizable differences in total factor productivity and output per worker. Our theory also suggests that productivity differences should be highest in medium-tech sectors, and that the trade regime and the degree of intellectual property right enforcement in the LDCs have an important effect on the direction of technical change and on productivity differences.